An attempt at quantitative evaluation of influence of genetic and environmental factors upon variability in blood pressure - Kowalik, Izabela (Anthropological Review, 1984)
The present paper is based upon material collected among 156 Polish rural families concerning systolic and diastolic blood pressure, sex, age, familial status, eventual ailments and disorders and anthropometry. The data were used first for estimating changes of blood pressure with. age by means of fitting linear regression equations to particular age segments. Sexual dimorphism in changes with age has been found. It has also been observed that in males aged 25 through: 54 years age has no relation to blood pressure which varies only under influence of other factors. (see table 2 and figure 1). The major purpose of the paper was to estimate components of variation in blood pressure: resulting from genetic variability and diversity of environmental influences. To this end an appropriate form of partitioning of variances has been applied to the data. Heritability was estimated. on two ways: 1. — from correlations between relatives (parent-offspring and sib-sib correlations. in various combinations: R — parent, D — offspring, M — mother, O — father, B — brother, S — sister), 2 — from replicability of measurements repeated several times on same subjects: (this method estimates upper limit of heritability coefficients). Comparison of results obtained on both ways shows that they are of equal value (e.g. h2 values for systolic pressure are 0.68 and 0.60, for diastolic 0.63 and 0.62 respectively by the first and the second method). At the same time it points to the substantial share of genetic variability in phenotypic variability of blood pressure. Further analysis of familial correlations and individual measurements distributions points toward effects of dominance with higher values being recessive (table 6, figure 3). This is not the clear-cut dominance. but as usual with quantitative traits a statistically significant tendency. Nonetheless suggestion of a recessive character of high blood pressure may be of some use for considerations upon causes of cardiovascular diseases. Genetic polymorphism and ecosensitivity of blood pressure (table 7) are similar to these found by other authors for body weight and seem to be as expected for a highly composite character. It is noteworthy to observe that there is no proof of sex linkage found in the present work (ligure 2). Results of the simple partitioning of variance into two components (obtained by analysis of replicability) point toward a fact that share of specific environmental conditions together with measurement error in the total phenotypic variance is large (over 3574), whereas only about 65%; of this variance is attributable to genetic variance and permanent environmental influences. The above said is equally true for systolic and for diastolic pressure.